2020
DOI: 10.21203/rs.3.rs-67649/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of Dark Fermentation Microbial Communities in the Light of Lactate and Butyrate Production

Abstract: Background: This study focuses on the processes occurring during acidogenic step of anaerobic digestion, especially resulting from nutritional interactions between dark fermentation (DF) bacteria and lactic acid bacteria (LAB). Previously, we have confirmed that DF microbial communities fed on molasses are able to convert lactate and acetate to butyrate in batch experiments. The aims of the study were: (i) to recognize biodiversity of DF microbial communities able and unable to convert lactate and acetate to b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(114 reference statements)
2
2
0
Order By: Relevance
“…It is illustrated by PBR3 (34 g COD of molasses/L), where the development of all groups of bacteria and a large variety of non-gaseous fermentation products were observed. On the other hand, a decrease of substrate concentration to 8.5 g COD of molasses/L inhibited the development of LAB in the microbial community (PBR2) that supports our current (PBR4) and previous (Detman et al, 2020) observations that sucrose stimulates LAB in DF consortia. Other factors preventing biomass accumulation and overproduction of SCFAs or alcohols are the HRT and the working volume that, together with the proper substrate concentration, ensure effective substrate utilization and gas release (Castelló et al, 2020).…”
Section: Other Factors Relevant For Hydrogen Productionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is illustrated by PBR3 (34 g COD of molasses/L), where the development of all groups of bacteria and a large variety of non-gaseous fermentation products were observed. On the other hand, a decrease of substrate concentration to 8.5 g COD of molasses/L inhibited the development of LAB in the microbial community (PBR2) that supports our current (PBR4) and previous (Detman et al, 2020) observations that sucrose stimulates LAB in DF consortia. Other factors preventing biomass accumulation and overproduction of SCFAs or alcohols are the HRT and the working volume that, together with the proper substrate concentration, ensure effective substrate utilization and gas release (Castelló et al, 2020).…”
Section: Other Factors Relevant For Hydrogen Productionsupporting
confidence: 91%
“…Recently, we have reported that the balance between LAB and butyrate-producing clostridia, and the pH conditions are the most relevant factors for the process of conversion of lactate and acetate to butyrate. Furthermore, the structure of the microbial communities most efficiently producing hydrogen presented here is comparable to the structure of consortia capable of conversion of lactate and acetate to butyrate (Detman et al, 2020). This supports the significance of the lactate and acetate conversion pathways in hydrogen-producing microbial communities postulated by other authors (Hung et al, 2007;Matsumoto and Nishimura, 2007;Yang et al, 2007;Jo et al, 2008;Juang et al, 2011;Wu et al, 2012;García-Depraect et al, 2017, 2019aGarcía-Depraect and León-Becerril, 2018;Palomo-Briones et al, 2018;Fuess et al, 2019).…”
Section: Lactic Acid Bacteria In Df Microbial Communitiessupporting
confidence: 88%
See 1 more Smart Citation
“…However, Liu et al proposed Clostridium sensu stricto 12 to be able to perform such a co-utilization (Liu et al, 2020). Furthermore, an experiment where organic substrate exclusively consisted of C2 and lactic acid was shown to enrich for both Clostridium sensu stricto 12 and Caproiciproducens while producing C4 (Detman et al, 2021). Thus, the co-utilization of C2 and lactic acid for the production of C4 may indeed have occurred in the DMB bioreactor.…”
Section: Primary Fermentation Products Lactic Acid and C2 Are Chain Elongated To Mcfas And C4 During Dcda Hydrolysate Metabolismmentioning
confidence: 99%